MRSA colonization and the nasal microbiome in adults at high risk of colonization and infection. Issue 6 (December 2015) - Bessesen, Mary T.; Kotter, Cassandra Vogel; Wagner, Brandie D.; Adams, Jill C.; Kingery, Shannon; Benoit, Jeanne B.; Robertson, Charles E.; Janoff, Edward N.; Frank, Daniel N.
Summary: Objective: The objective of this study was to define the nasal microbiome of hospital inpatients who are persistently colonized with methicillin-resistant Staphylococcus aureus (MRSA) compared with matched, non-colonized controls. Methods: Twenty-six persistently MRSA-colonized subjects and 26 matched non-colonized controls were selected from the screening records of the infection control program at the Department of the Veteran Affairs Eastern Colorado Health Care System (VA-ECHCS). The nasal microbiotas were analyzed with PCR amplification and sequencing of the 16S ribosomal RNA (rRNA) gene. Comparison of all variables across the groups was performed using stratified logistic regression to account for the one-to-one matching. Canonical discriminant analysis was performed to assess differences in bacterial community across the two groups. Competing organisms were cocultured with MRSA in vitro. Results: There was a negative association between MRSA colonization and colonization with Streptococcus spp. At the species level, multivariate analysis demonstrated a statistically significant negative association between colonization with Streptococcus mitis or Lactobacillus gasseri and MRSA. Coculture experiments revealed in vitro competition between S. mitis and all of the 22 MRSA strains isolated from subjects. Competition was blocked by addition of catalase to the media. Persistently colonized subjects had lesser microbial diversity than the non-colonized controls. Conclusion: In a high-risk inpatient setting, bacterial competition in the nasal niche protects some patients from MRSA colonization. Highlights: Streptococcus mitis and Lactobacillus gasseri are associated with decreased MRSA colonization. Decreased nasal bacterial diversity is associated with MRSA colonization. S. mitis inhibits the growth of MRSA by a hydrogen peroxide-mediated mechanism.